Beyond Observance: The Role of Medical Colleges in Transforming Health Days - Masood, Jamal; Chaturvedi, Ruchi (Indian Journal of Community Health, 2024)
The observance of health days, ranging from World Health Day to those dedicated to specific health conditions, serves as a valuable opportunity to improve health literacy among the population and catalyse positive behavioural change. These designated days act as platforms for spreading awareness on a wide range of health issues, from prevention strategies to treatment methods . They encourage us to reflect on the progress we’ve made, recognize the challenges we still face, and inspire collective action to address pressing health concerns.